What Mapai stands for : highlights of the platform to the fourth Knesset of Mapai - The Israel Labour Party. - MAPAI-Israel Labour Party (Tel-Aviv : MAPAI, 1959)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: joodse arbeidersbeweging; Israël